Free-span identification of buried gas pipe subjected to sine sweep load in pipe. (15th October 2020) - Liao, Ningsheng; Zhang, Hang; Yu, Dongliang; Feng, Shulu; Zhang, Shimin
Highlights: Free span of buried gas pipeline can be inspected by the proposed method. Location and exact length of free span can be calculated. Frequency response characteristic (FRC) and weighted response signal energy (WRSE) can be used to identify free span. Sine sweep speed of excitation signal and moving speed of free span detector play an important role in free span detection. Abstract: Free span along a buried gas pipeline is inevitable since the buried gas pipeline is constantly exposed to the complex surrounding environment. A free span is commonly identified by manual inspection, sonar technology, or a remote robot. The main disadvantage of these identification methods is that the detection process is significantly interfered with by pipeline surrounding environment. In this paper, free-span identification of a buried gas pipeline subjected to a sine sweep load inside the pipe is experimentally studied. Two critical parameters, the sine sweep rate of an excitation signal and the moving speed of a free span detector, are experimentally researched in order to explore their impact on free-span identification results. The frequency response characteristics and the weighted response signal energy are adopted as evaluation indexes to analyze the location and length of a free span. Both static and moving experiments were carried out to verify the capability of detecting a free span under the moving state of a free span detector, the reliability of the two evaluation indexes. The experimental results show that location and length of a free span along a buried gas pipe can be identified.